2016
DOI: 10.3389/fpubh.2016.00208
|View full text |Cite
|
Sign up to set email alerts
|

Legal Framework and Retirement Policies in Serbia from 1990 to 2016 – Gendered Perspective

Abstract: Retirement policy is an unavoidable factor for the economic and social stability of the state. In our country, Serbia, the total number of pensioners in 2015 was almost 1.8 million, which is higher in comparison to the time period from 2002 to 2014. According to increased number of pensioners, pension reforms are a crucial step of economic stability for less developed country, such as Serbia. The first step in this question in Serbia was made in 2001, and this change was referred to the raise in the retirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The purpose of these occasionally harsh policies is at least partially to compensate the loss of labor market size due to advanced population aging. Mandatory legal retirement age was moving in Europe from approximately 55 toward 65 in women, while in men, such approach preceded for many years ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of these occasionally harsh policies is at least partially to compensate the loss of labor market size due to advanced population aging. Mandatory legal retirement age was moving in Europe from approximately 55 toward 65 in women, while in men, such approach preceded for many years ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also revealed that, surprisingly, physicians from the Serbian capital Belgrade demonstrated less factual knowledge regarding the fragile X gene premutation than their colleagues from the rest of country. Belgrade's greater reliance on secondary and tertiary healthcare institutions compared to the rest of the country (Jovanovic, 2016 ) could partially explain such surprising gaps. According to Riley and Wheeler ( 2017 ), it is necessary to identify the public health system issues and barriers in the FXD field in order to move future activities in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Women's labour market inactivity in Serbia reflects broader gender norms: the extent of their unpaid work in households, inadequate support to women in reconciling work and family responsibilities, employers' discriminatory treatment of young women, the existing wage gap, women's lower statutory retirement age, as well as the existence of a statutory minimum social insurance contributions base which discourages formal part-time work, an option more commonly used by women with family responsibilities in other countries (Government of the Republic of Serbia 2016). The differences between men's and women's participation are most visible in older age groups (from 55 to 64 years), among those with low education, and in rural settlements (Milovanovic et al 2016).…”
Section: Employment Policiesmentioning
confidence: 99%